2021
DOI: 10.1002/alz.12463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increased APP gene dose in Down syndrome and the Dp16 mouse model

Abstract: Introduction:People with Down syndrome (DS) are predisposed to Alzheimer's disease (AD). The amyloid hypothesis informs studies of AD. In AD-DS, but not sporadic AD, increased APP copy number is necessary, defining the APP gene dose hypothesis.Which amyloid precursor protein (APP) products contribute needs to be determined. Methods: Brain levels of full-length protein (fl-hAPP), C-terminal fragments (hCTFs), and amyloid beta (Aβ) peptides were measured in DS, AD-DS, non-demented controls (ND), and sporadic AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 177 publications
(389 reference statements)
5
38
0
Order By: Relevance
“…Thus differences in human and mouse fibroblast biology are likely to underlie our observation that in MEFs isolated from two DS mouse models no alteration in endosomal biology was detected. Endosome enlargement is reported to occur both in the entorhinal cortex and medial septum in the Dp1Yey DS mouse model, which is genetically similar to the Dp1Tyb model [ 18 ]. This suggests that differences in the biology between fibroblasts and cells within these brain regions influence this important DS associated phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus differences in human and mouse fibroblast biology are likely to underlie our observation that in MEFs isolated from two DS mouse models no alteration in endosomal biology was detected. Endosome enlargement is reported to occur both in the entorhinal cortex and medial septum in the Dp1Yey DS mouse model, which is genetically similar to the Dp1Tyb model [ 18 ]. This suggests that differences in the biology between fibroblasts and cells within these brain regions influence this important DS associated phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could quantify APP expression in Dp1Tyb primary neurons to determine whether the lack of App dosage sensitivity in MEFs is a result of the embryonic origin of the cells, or because of cell-type specific biology. Previous studies have been inconsistent on the dosage sensitivity of APP in different tissues and models, suggesting that APP production is tightly regulated [ 18 , 42 44 ]. Since three copies of APP are sufficient for AD development and APP is the precursor of amyloid-β [ 1 ], studying the regulation of APP expression in different tissues and over time could be pivotal to gain further understanding of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific pathology of TMCC2 staining in Down syndrome may relate to over-expression of APP, its proteolytic products, or be associated with one or more of the 200-300 other genes present on chromosome 21 which will also be present in excess. In this respect, it has been noted in mouse models of trisomy 21 as well as in iPSC-derived Down syndrome neurons, that chromosome 21 genes other than APP exacerbate AD pathogenesis (Wiseman et al, 2018;Ovchinnikov et al, 2018;Sawa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While triplication of APP is thought to be a main driver of DS-AD, Lockstone et al found no evidence of increased APP abundance in the brain of adults who had DS [ 58 ]. In contrast, more recent studies have shown robust up-regulation of APP transcript and protein in the brains of individuals with DS and DS-AD [ 122 , 123 ]. The expression of other Hsa21 genes, including DYRK1A , ADAMTS1 , BACE2 , RCAN1 , and non-Hsa21 genes of interest, including APOE and NOTCH2 , is also increased in the brains of adults who have DS [ 58 ].…”
Section: Ds-ad Mouse Models and Human Tissuementioning
confidence: 99%